Frailty assessment using routine clinical data: An integrative review. (March 2022) - Lim, Arum; Choi, JiYeon; Ji, Hyunju; Lee, Hyangkyu
Highlights: Routine clinical data-based frailty tools have been suggested as a pragmatic approach. The items of routine clinical data-based tools were generally biased toward frailty's risk factors. Routine clinical data-based frailty tools will be useful to identify frail adults in clinical settings. Abstract: Background: Frailty is a common but complex problem in older adults. Frailty assessment using routine clinical data has been suggested as a pragmatic approach based on electronic health records from primary care center or hospital settings. Purpose: We aimed to explore the tools and outcome variables used in the published studies on frailty assessment using routine clinical data. Methods: An integrative literature review was conducted using the method of Whittemore and Knafl. A literature search was conducted in PubMed, EMBASE, and CINAHL from January 2010 to October 2021. Results: A total of 45 studies and thirteen frailty assessment tools were analyzed. The assessment items were generally biased toward frailty's risk factors rather than the mechanisms or phenotypes of frailty. Similar to using conventional tools, routine clinical data-based frailty was associated with adverse health outcomes. Conclusions: Frailty assessment based on routine clinical data could efficiently evaluate frailty using electronic health records from primary care centers or hospitals. However, they need refinement to consider the risk factors, mechanisms, and frailty phenotypes.